Stem morpho-anatomy of Baccharis cylindrica (Less.) DC. (Asteraceae) (Revista Brasileira de Ciências Farmacêuticas, 2004)
Baccharis cylindrica (Less.) DC. (Asteraceae) is a three-winged stem species, which belongs to the Trimera group and is commonly named as carqueja, as well as several other species of Baccharis. It is employed in the traditional medicine as stomachic and diuretic. This work has carried out the stem morpho-anatomical analysis of the medicinal plant, in order to contribute to its identification and to the knowledge for the Trimera group. Stem fragments were collected, fixed and prepared according to usual optical and scanning electron microtechniques. The epidermis is uniseriate, coated by striated cuticle and has anomocytic stomata, pluricellular glandular and non-glandular trichomes. In the wings, chlorenchyma, composed of palisade parenchyma beneath both epidermal faces and spongy parenchyma in the middle, and collateral vascular bundles are seen. In the stem axis, angular collenchyma alternating with chlorenchyma, included phloem, secretory ducts and calcium oxalate styloids are also observed.